2009
DOI: 10.1103/physrevb.80.115418
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical characterization of carbon nanotubes in torsion via symmetry adapted tight-binding objective molecular dynamics

Abstract: The nonlinear elastic response of carbon nanotubes ͑CNTs͒ in torsion is derived with objective molecular dynamics and a density-functional-based tight-binding model. The critical strain beyond which CNTs behave nonlinearly, the most favorable rippling morphology, and the twist-and morphology-related changes in fundamental band gap are identified from a rigorous atomistic description. There is a sharply contrasting behavior in the electronic response: while in single-walled CNTs the band-gap variations are domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 33 publications
7
68
1
Order By: Relevance
“…This implies that the tube buckled in the (2,1) mode at c ¼ 4.6%. Using objective MD, Zhang et al 26 found a similar bifurcation in the potential energy for infinitely long (12,12) SWCNT deformed in torsion. Their critical value of the shear strain, 6.2%, is about 30% higher than the present value of 4.6%.…”
Section: Fig 2 Various Morphologies Ofmentioning
confidence: 97%
See 3 more Smart Citations
“…This implies that the tube buckled in the (2,1) mode at c ¼ 4.6%. Using objective MD, Zhang et al 26 found a similar bifurcation in the potential energy for infinitely long (12,12) SWCNT deformed in torsion. Their critical value of the shear strain, 6.2%, is about 30% higher than the present value of 4.6%.…”
Section: Fig 2 Various Morphologies Ofmentioning
confidence: 97%
“…23 . The exponent 1.23 is between 1.5 obtained by Yakobson et al 2 and 0.99 by Zhang et al 26 which could be due to the consideration of finite length SWCNTs with clamped ends. From Fig.…”
Section: Fig 2 Various Morphologies Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The salient feature of carbon nanotubes is their mechanical robustness and resilience [6]: Due to the extremely large stiffness, for instance, their thermal conductivity becomes higher than even that of diamond [7]. Besides, their flexibility in bending [8,9], twisting [9,10,11,12], radial compression [13,14,15,16,17], and the associated variations in the physical properties hold promise for developing nanoelectromechanical devices [18,19]. Towards successful implementations of such ideas, computational studies have been playing a vital role in complementing experimental observations, often difficult and incomplete for nanomaterials [20].…”
Section: Introductionmentioning
confidence: 99%